Experimental investigation on frequency shifting of imperfect adhesively bonded pipe joints - Haiyam, F. N.; Hilmy, Irfan; Sulaeman, Erwin; Mohamed Ariff, Tasnim Firdaus; Adesta, Erry Yulian Triblas (IOP Publishing, 2018)
Inspection tests for any manufactured structure are compulsory in order to detect the existence of damage.It is to ensure the product integrity, reliability and to avoid further catastrophic failure. In this research, modal analysis was utilizedto detect structural damage as one of the Non Destructive Testing (NDT) methods. Comparingthe vibration signal of a healthy structure with a non-healthy signalwas performed. A modal analysis of an adhesively bonded pipe joint was investigated with a healthy joint as a reference. The damage joint was engineered by inserting a nylon fiber, which act as an impurity at adhesive region. The impact test using hammer was utilized in this research. Identification of shifting frequency of a free supported and clamped pipe joint was performed.It was found that shiftingfrequency occurred to the lower side by 5%.